Determining of The Compliance of Local Governments To Implement The Accounting System of The Government’s Accrual Base In Indonesia - Agung Nur Probohudono; Wahyu Widayat; Siti Arifah (Yayasan Ilomata, 2020)
This study refers to the influence of the age of local government, status, number of Regional Device Task Force (SKPD), financial autonomy ratios, effectiveness ratios, local income growth ratios, and the quality of local financial reports that exist in local governments as an independent variable on the compliance of local governments to implement government accounting systems as the dependent variable. Using quantitative methods with secondary data obtained from information on the publication of the Indonesian Financial Audit Agency, the Central Bureau of Statistics of the Republic of Indonesia (BPS), and local government reports. The sample used is limited to the municipal and district governments in western Indonesia, which are being evaluated by the Indonesian Financial Audit Agency in the implementation of an accrual base government accounting system of 158 local governments namely 36 cities and 122 districts. Multiple linear regression analysis was used to test the hypothesis. The research is a causality, quantitative research model, and secondary data from local governments throughout Indonesia and secondary data about the compliance of local governments in the application of Government Accounting Standards (SAP) published by the Audit Board of the Republic of Indonesia (BPK). The results of the hypothesis analysis conclude that the status of local government, the ratio of regional government autonomy, and the growth of local revenue significantly influence the compliance of local governments in the implementation of the accrual base government accounting system.